'Trying, failing, succeeding, and trying again and again': perspectives of teachers of pupils with severe profound multiple learning difficulties. Issue 2 (15th March 2017) - Jones, Phyllis; Riley, Michael W.
Abstract: This article explores the perspectives of seven teachers in England who teach pupils with severe profound and multiple learning difficulties about their learning to teach this group of students. Teachers' views were captured through a combination of synchronous and asynchronous online communications. Four themes emerged from teachers' perspectives about their own learning: learning through doing in the classroom, learning through self-inquiry and research, learning from and with others and more formal learning opportunities. A constructivist approach to teacher learning is affirmed as a helpful lens to further understand how teachers learn to teach pupils with complex learning profiles. The article supports teacher learning as a holistic process that takes place throughout teachers' careers. It highlights the value teachers place on learning through doing in the classroom, learning through self-inquiry and research, learning from and with others, as well as formal learning.